Vitamin D Reduces Thyroid Cancer Cells Migration Independently From the Modulation of CCL2 and CXCL8 Chemokines Secretion - Coperchini, Francesca; Greco, Alessia; Croce, Laura; Petrosino, Elena; Grillini, Beatrice; Magri, Flavia; Chiovato, Luca; Rotondi, Mario (Frontiers in Endocrinology, 2022)
Background: Vitamin-D3 is largely involved in the regulation of calcium homeostasis. More recently, it was demonstrated that Vitamin-D exerts several beneficial effects against cancer progression through several mechanisms, including the reduction of cancer cells proliferation and migration. CXCL8 and CCL2 are two chemokines secreted by thyroid tumor cells. In the thyroid tumor microenvironment, these chemokines exert several pro-tumorigenic effects including the one to increase the metastatic potential. The aim of the present study was to investigate if Vitamin-D could modulate both thyroid cancer cells migration as well as their ability to secrete CCL2 and CXCL8. Methods: TPC-1 (RET/PTC rearranged) and 8505C (BRAFV600e mutated) thyroid cancer cell lines were treated with increasing concentration of 1,25-OH-Vitamin-D3 (0-1000 nM). Cell viability was assessed by WST-1 assay, cell migration was evaluated by transwell-migration chamber system and CCL2 and CXCL8 levels were measured in the cell cultures supernatants by ELISA. Results: Vitamin-D did not affect cell viability but reduced, in a dose-dependent and significant manner, thyroid cancer cells migration (ANOVAs p<0.05 for both TPC-1 and 8505c). Vitamin-D differently modulated the secretion of CCL2 and CXCL8, by significantly inhibiting the secretion of CCL2 in both thyroid cancer cell lines and inhibiting the secretion of CXCL8 only in TPC-1(ANOVAs p<0.05). Conclusions: Vitamin-D treatment of thyroid cancer cell lines reduces cell migration independently from the inhibition of the secretion of pro-tumorigenic chemokines. Future studies specifically designed at clarifying the pathways involved in the different inhibitory effects of Vitamin-D on CCL2 and CXCL8 in thyroid cancer cells appear worthwhile.